Some issues concerning the dynamic response and damage of composite laminates subjected to low velocity impact - Ghelli, Daniele <1979> (Alma Mater Studiorum - Università di Bologna, 2009)
Abstract. This thesis presents a discussion on a few specific topics regarding the low velocity impact behaviour of laminated composites. These topics were chosen because of their significance as well as the relatively limited attention received so far by the scientific community. The first issue considered is the comparison between the effects induced by a low velocity impact and by a quasi-static indentation experimental test. An analysis of both test conditions is presented, based on the results of experiments carried out on carbon fibre laminates and on numerical computations by a finite element model. It is shown that both quasi-static and dynamic tests led to qualitatively similar failure patterns; three characteristic contact force thresholds, corresponding to the main steps of damage progression, were identified and found to be equal for impact and indentation. On the other hand, an equal energy absorption resulted in a larger delaminated area in quasi-static than in dynamic tests, while the maximum displacement of the impactor (or indentor) was higher in the case of impact, suggesting a probably more severe fibre damage than in indentation. Secondly, the effect of different specimen dimensions and boundary conditions on its impact response was examined. Experimental testing showed that the relationships of delaminated area with two significant impact parameters, the absorbed energy and the maximum contact force, did not depend on the in-plane dimensions and on the support condition of the coupons. The possibility of predicting, by means of a simplified numerical computation, the occurrence of delaminations during a specific impact event is also discussed. A study about the compressive behaviour of impact damaged laminates is also presented. Unlike most of the contributions available about this subject, the results of compression after impact tests on thin laminates are described in which the global specimen buckling was not prevented. Two different quasi-isotropic stacking sequences, as well as two specimen geometries, were considered. It is shown that in the case of rectangular coupons the lay-up can significantly affect the damage induced by impact. Different buckling shapes were observed in laminates with different stacking sequences, in agreement with the results of numerical analysis. In addition, the experiments showed that impact damage can alter the buckling mode of the laminates in certain situations, whereas it did not affect the compressive strength in every case, depending on the buckling shape. Some considerations about the significance of the test method employed are also proposed. Finally, a comprehensive study is presented regarding the influence of pre-existing in-plane loads on the impact response of laminates. Impact events in several conditions, including both tensile and compressive preloads, both uniaxial and biaxial, were analysed by means of numerical finite element simulations; the case of laminates impacted in postbuckling conditions was also considered. The study focused on how the effect of preload varies with the span-to-thickness ratio of the specimen, which was found to be a key parameter. It is shown that a tensile preload has the strongest effect on the peak stresses at low span-to-thickness ratios, leading to a reduction of the minimum impact energy required to initiate damage, whereas this effect tends to disappear as the span-to-thickness ratio increases. On the other hand, a compression preload exhibits the most detrimental effects at medium span-to-thickness ratios, at which the laminate compressive strength and the critical instability load are close to each other, while the influence of preload can be negligible for thin plates or even beneficial for very thick plates. The possibility to obtain a better explanation of the experimental results described in the literature, in view of the present findings, is highlighted. Throughout the thesis the capabilities and limitations of the finite element model, which was implemented in an in-house program, are discussed. The program did not include any damage model of the material. It is shown that, although this kind of analysis can yield accurate results as long as damage has little effect on the overall mechanical properties of a laminate, it can be helpful in explaining some phenomena and also in distinguishing between what can be modelled without taking into account the material degradation and what requires an appropriate simulation of damage.